Ventricular Septal Defect as a Complication of TAVI: Mechanism and Incidence. Issue 3 (4th May 2018) - Zeniou, Vicki; Chen, Shmuel; Gilon, Dan; Segev, Amit; Finkelstein, Arik; Planer, David; Barbash, Israel; Halkin, Amir; Beeri, Ronen; Lotan, Chaim; Danenberg, Haim D.
ABSTRACT: Background: Transcatheter aortic valve implantation (TAVI) is the treatment of choice in patients with severe symptomatic aortic stenosis and high surgical risk. Ventricular septal defect (VSD) is a rare complication of TAVI acquired peri-procedurally. This study examines the incidence and possible mechanisms of TAVI-associated VSD. Methods: A multicenter, retrospective study of 400 patients who underwent TAVI in 2015 was conducted. All patients were evaluated with transthoracic echocardiography before and after the procedure. Results: Six subjects (1.5%) were found to have new VSD. Five of them had severe aortic valve calcification. Three patients (50%) were implanted with the Sapien valve (Edwards Lifesciences, Irvine, CA, USA) and the other three with Corevalve valve (Medtronic, Minneapolis, MN, USA). Four patients had a membranous type of VSD, and two patients had a muscular type apical VSD. All six cases were diagnosed to have a small, restrictive left to right shunt, with minimal hemodynamic significance. The patients were not symptomatic and therefore did not require any further intervention. Two mechanisms are proposed for VSD formation: pressure exerted directly by the valve on the membranous septum, and penetration of the apical septum by the stiff wire. Conclusion: VSD is a rare complication of TAVI that may involve the membranous or the muscular interventricular septum. Hemodynamic and clinical sequelae are mostly benign. Proper imaging techniques and proper devices to further decrease VSD formation incidence post-TAVI have yet to be determined.